Models of Land Ownership in Islam: Analysis on Hadis Ihyā’ al-Mawāt - Ahmad Suhendra (UIN Sunan Kalijaga Yogyakarta, 2017)
This article discusses land ownership from the perspective of tradition, especially the tradition of the revival of the dead earth (Iḥya ‘al-Mawāt). This relates to the land conflicts that often occur, so it requires a religious perspective in land ownership. Therefore, the issue raised is how the ownership of land in the Hadith? How Hadith provide a solution to the land dispute? To answer it used historical approach, hermeneutic, and sociology. Turns ownership in Islam there are three, namely individual ownership, common ownership and state ownership. Islam recognizes individual ownership is perfect (al-milk al-tāmm) and imperfect (al-milk al-nāqis). Criteria of land ownership in the Hadith oriented aspects of justice and benefits (maslaḥlah). Hadith Iḥya ‘al-Mawāt give you an idea that the Prophet prevent conflicts caused by land disputes by explaining the status and ownership of land with cultural framework. Efforts were made persuasively by a cultural approach, in addition to the structural approach.[Artikel ini membahas tentang kepemilikan tanah dari perspektif tradisi, terutama tradisi kebangkitan kembali bumi yang mati (Iḥya ‘al-Mawāt). Hal ini berkaitan dengan konflik tanah yang kerap terjadi, sehingga membutuhkan perspektif agama dalam kepemilikan tanah. Karena itu, masalah yang diangkat adalah bagaimana kepemilikan tanah dalam Hadis? Bagaimana Hadis memberikan solusi terhadap sengketa tanah? Untuk menjawabnya digunakan pendekatan historis, hermeneutik, dan sosiologi. Ternyata kepemilikan dalam Islam ada tiga, yaitu kepemilikan individu, kepemilikan bersama dan kepemilikan negara. Islam mengakui kepemilikan individu sempurna (al-milk al- tāmm) dan tidak sempurna (al-milk al-nāqis). Kriteria kepemilikan tanah dalam hadis berorientasi aspek keadilan dan tunjangan (maslaḥlah). Hadis Iḥya ‘al-Mawāt memberi Anda gagasan bahwa Nabi mencegah konflik yang disebabkan oleh sengketa tanah dengan menjelaskan status dan kepemilikan tanah dengan kerangka budaya. Upaya dilakukan secara persuasif dengan pendekatan budaya, disamping pendekatan struktural.]